1990
DOI: 10.1007/bf00171838
|View full text |Cite
|
Sign up to set email alerts
|

Activity of intravenous menogaril in patients with previously untreated metastatic breast cancer

Abstract: We have carried out a phase II study of intravenous menogaril given every four weeks in a group of patients with breast cancer who had received no prior chemotherapy for metastatic disease. Myelosuppression, nausea and vomiting and local reactions were seen frequently. Six partial responses (median duration 154 days) were seen in 24 eligible patients. We conclude menogaril is active in breast cancer and recommend that because it can be delivered in high doses orally, future trials in this disease should focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1991
1991
1994
1994

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, 3 patients achieved stable disease for > 8 months with documented clinical improvement evidenced by improved performance status, discontinuation of opiates, and decreased use of nonnarcotic analgesics. The drug was well tolerated except for myelotoxicity which was more common and severe in this study than in other menogaril trials at higher doses [5,6]. The responses observed in phase II studies using menogaril have been low with the best responses observed in lymphoma and breast cancer [5,6].…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Interestingly, 3 patients achieved stable disease for > 8 months with documented clinical improvement evidenced by improved performance status, discontinuation of opiates, and decreased use of nonnarcotic analgesics. The drug was well tolerated except for myelotoxicity which was more common and severe in this study than in other menogaril trials at higher doses [5,6]. The responses observed in phase II studies using menogaril have been low with the best responses observed in lymphoma and breast cancer [5,6].…”
Section: Discussionmentioning
confidence: 49%
“…The drug was well tolerated except for myelotoxicity which was more common and severe in this study than in other menogaril trials at higher doses [5,6]. The responses observed in phase II studies using menogaril have been low with the best responses observed in lymphoma and breast cancer [5,6]. The absence of measurable responses in this study may be partially due to the lack of dose intensification since the starting dose was 40 mg/m 2 lower than used in other studies [5,6].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation